(untitled) (Journal of Educational Sciences, 2025)
Recently, the rapid development of information and communication technology necessities have raised the quality of education to a new level. Therefore, this article examines ways to develop students’ abilities to utilise information technologies through enhancing media literacy in the process of teaching biology. Media literacy among tenth-grade students makes it possible to explain complex biological topics in a clear and engaging manner, as well as to develop skills for creatively presenting their academic work. In the process of teaching biology, media education methods become an important tool for improving both biological knowledge and media literacy of students. The article researches several online platforms that contribute to the formation of media literacy among learners, such as Heyzine, an online platform that allows the creation of interactive and multimedia content, and LearningApps.org, an online platform designed for creating, using, and sharing interactive tasks and exercises. The purpose of the study is to identify students’ needs through a survey and to apply methods that enhance schoolchildren’s media literacy. The survey was conducted using the Google Forms application and was carried out at Boarding School No. 3 in Shymkent. As a result of the survey of tenth-grade students, information technologies that contribute to the development of media literacy were identified, and methods of working with these platforms were analyzed. The research findings demonstrate that the use of effective approaches to media literacy formation in biology education promotes the development of students’ creative abilities and increases their interest in the subject. Keywords: media literacy, media education, students, information, technology, biology.